Content Analysis of Bahasa Indonesia Textbook for Indonesian Language - Wiratikusuma, Fransiska (Jurnal Pendidikan Bahasa dan Sastra, 2024)
As the official language, Indonesian language has a key position in the curriculum of Indonesia, including in from the language policy, education system, class schedule, the national main curriculum assessment, etc. The Indonesian language textbooks for first grade Junior High School is compiled based on the curriculum objectives and contents stipulated in the constitution of the country. The compilation and development of this Indonesian language textbooks also refer to the teaching design of content and Integrated Language Learning (CLIL) to prepare and design the content of textbooks. The four aspects in the subtopics, i.e., ‘language comprehension ability’, ‘language summary or restatement ability’, ‘language analysis ability’ and ‘language listening, speaking, reading, writing and practice ability’, are consistent with the four factors of ‘content’, ‘cognition’, ‘communication’, and ‘culture’ in CLIL.